VICTIM RIGHTS IN THE DIGITAL AGE: LEGAL FRAMEWORKS FOR PROTECTING ONLINE ABUSE SURVIVORS - Iwan Rasiwan (Law Studies and Justice Journal (LAJU), 2025)
Online violence against vulnerable groups is increasing, but evaluation of the effectiveness of the law in providing justice and restitution for victims is still limited. This study examined the effectiveness of the implementation of laws related to online violence in providing protection and compensation to victims in various jurisdictions. The research method was carried out by means ofSystematic Literature Review with PRISMA 2020 protocol, using Scopus, Web of Science databases. Thematic coding analysis to identify patterns of legal effectiveness and implementation challenges.Of the 19 articles, the effectiveness of the law is highly dependent on the context of the judicial system, institutional capacity, and national regulatory framework. Approachvictim centered showing a more effective response, but the implementation of victims' rights is still uneven and support is inadequate.Legal protection for victims of online violence remains fragmented and inconsistent globally. Regulation based on victim centered justice potentially increases justice and protection. Further research is suggested to focus on empirical experiences of victims.